1999
DOI: 10.1136/bmj.319.7203.147
|View full text |Cite
|
Sign up to set email alerts
|

Breast feeding and obesity: cross sectional study

Abstract: Objective To assess the impact of breast feeding on the risk of obesity and risk of being overweight in children at the time of entry to school. Design Cross sectional survey Setting Bavaria, southern Germany. Methods Routine data were collected on the height and weight of 134 577 children participating in the obligatory health examination at the time of school entry in Bavaria. In a subsample of 13 345 children, early feeding, diet, and lifestyle factors were assessed using responses to a questionnaire comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
410
12
39

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 742 publications
(499 citation statements)
references
References 20 publications
38
410
12
39
Order By: Relevance
“…girls who were v. those never breast-fed had a 50 % reduced odds of being overweight/obese. Breast-feeding as an independent variable showed a modest inverse, linear association with BMI and waist circumference among these children of pre-school age, and this concurs with prior childhood studies (14)(15)(16) . More recently, the Avon Longitudinal Study of Parents and Children (n 4852) found that longer breast-feeding duration was associated with lower mean BMI (P trend , 0?001) (16) .…”
Section: Discussionsupporting
confidence: 88%
“…girls who were v. those never breast-fed had a 50 % reduced odds of being overweight/obese. Breast-feeding as an independent variable showed a modest inverse, linear association with BMI and waist circumference among these children of pre-school age, and this concurs with prior childhood studies (14)(15)(16) . More recently, the Avon Longitudinal Study of Parents and Children (n 4852) found that longer breast-feeding duration was associated with lower mean BMI (P trend , 0?001) (16) .…”
Section: Discussionsupporting
confidence: 88%
“…Ekelund et al (34) emphasized that participants who had been breast-fed for more than 6 months benefited from maternal breast-feeding in terms of MetS prevention. Breast-feeding offers some protection related to the development of obesity (35) . Considering that breast-fed infants gain weight more slowly over the first year compared with Table 3 Multiple logistic regression analysis of metabolic syndrome components and its associated factors in 7-to 17-year-old children and adolescents (n 1770), Guangzhou, China, …”
Section: Discussionmentioning
confidence: 99%
“…A positive family history of overweight and obesity is an important indicator of the genetic risk for being overweight in childhood. 46,47 However, besides inheritance of genes that confer susceptibility to obesity, parental overweight is also a proxy for shaping the postnatal eating and activity environment of their child. In most cases overweight parents create and sustain an 'obesogenic' environment (that is, high-caloric diets and physical inactivity) for themselves and their children.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 The association between maternal education and childhood overweight at 3-5 years of age observed in the present study accords with the findings from other similar studies. 15,46,57,58 In all these studies preschoolers born to mothers having a higher education (usually with a college or a university degree) were less likely to be overweight than children born to mothers with lower education (usually with a junior high school degree). Higher maternal educational level in most cases reflects higher socioeconomic status of the family, which has been associated with healthier dieting, physical activity and weight control practices compared to families with lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%